Comparative Efficacy of 177Lu and 90Y for Anti-CD20 Pretargeted Radioimmunotherapy in Murine Lymphoma Xenograft Models - Frost, Sofia H. L.; Frayo, Shani L.; Miller, Brian W.; Orozco, Johnnie J.; Booth, Garrett C.; Hylarides, Mark D.; Lin, Yukang; Green, Damian J.; Gopal, Ajay K.; Pagel, John M.; Bäck, Tom A.; Fisher, Darrell R.; et al. (PLOS ONE, 2015)
Purpose Pretargeted radioimmunotherapy (PRIT) is a multi-step method of selectively delivering high doses of radiotherapy to tumor cells while minimizing exposure to surrounding tissues. Yttrium-90 (90Y) and lutetium-177 (177Lu) are two of the most promising beta-particle emitting radionuclides used for radioimmunotherapy, which despite having similar chemistries differ distinctly in terms of radiophysical features. These differences may have important consequences for the absorbed dose to tumors and normal organs. Whereas 90Y has been successfully applied in a number of preclinical and clinical radioimmunotherapy settings, there have been few published pretargeting studies with 177Lu. We therefore compared the therapeutic potential of targeting either 90Y or 177Lu to human B-cell lymphoma xenografts in mice. Methods Parallel experiments evaluating the biodistribution, imaging, dosimetry, therapeutic efficacy, and toxicity were performed in female athymic nude mice bearing either Ramos (Burkitt lymphoma) or Granta (mantle cell lymphoma) xenografts, utilizing an anti-CD20 antibody-streptavidin conjugate (1F5-SA) and an 90Y- or 177Lu-labeled 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA)-biotin second step reagent. Results The two radionuclides displayed comparable biodistributions in tumors and normal organs; however, the absorbed radiation dose delivered to tumor was more than twice as high for 90Y (1.3 Gy/MBq) as for 177Lu (0.6 Gy/MBq). More importantly, therapy with 90Y-DOTA-biotin was dramatically more effective than with 177Lu-DOTA-biotin, with 100% of Ramos xenograft-bearing mice cured with 37 MBq 90Y, whereas 0% were cured using identical amounts of 177Lu-DOTA-biotin. Similar results were observed in mice bearing Granta xenografts, with 80% of the mice cured with 90Y-PRIT and 0% cured with 177Lu-PRIT. Toxicities were comparable with both isotopes. Conclusion 90Y was therapeutically superior to 177Lu for streptavidin-biotin PRIT approaches in these human lymphoma xenograft models.